Exploring the anti‑inflammatory activity of boron compounds through the miR‑21/PTEN/AKT pathway in cecal ligation and puncture‑induced sepsis - Sevim, Çiğdem; Özkaraca, Mustafa; Kara, Mehtap; Taghizadehghalehjoughi, Ali; Genç, Sidika; Yeni, Yesim; Mendil, Ali Sefa; Spanakis, Marios; Özçağli, Eren; Kuzmin, Sergey V.; Spandidos, Demetrios A.; Tsatsakis, Aristides (Spandidos Publications, 2024)
The present study investigated the impact of boric acid (BA) and borax (BX) on markers of inflammation and modifications in miR‑21/PTEN/AKT pathway genes in the liver and kidney tissues of Sprague Dawley male rats with sepsis induced by cecal ligation and puncture (CLP). A total of 60 male Sprague Dawley rats were randomly divided into 6 groups, each containing 10 animals as follows: Control, CLP (where the model was created), 20 mg/kg BX (CLP + BX1), 40 mg/kg BX (CLP + BX2), 20 mg/kg BA (CLP + BA1) and 40 mg/kg BA (CLP + BA2). Liver and kidney tissues were analyzed for histopathological changes, immunopositivity for tumor necrosis factor‑α, interleukin (IL)‑6 and IL‑10, and gene expression of microRNA‑21 (miR‑21), phosphatase and tensin homolog (PTEN) and AKT. Gene expression analysis in the liver tissues revealed a significant decrease in miR‑21, and a marked but not significant decrease in PTEN levels in the CLP group, while AKT expression was significantly increased in the CLP group, and was significantly decreased in CLP + BA1 group compared with in the CLP group. In the kidney tissues, miR‑21 levels were significantly decreased in the CLP group, but the CLP + BA2 group showed a significant increase compared with in the CLP group. These results suggest the potential therapeutic benefits of low‑dose BA and BX in ameliorating sepsis‑induced tissue damage, emphasizing the need for further exploration of their mechanisms of action.
Keywords: Male; Anti-Inflammatory Agents; Punctures; Kidney; sepsis; Rats, Sprague-Dawley; borax; Sepsis; cytokine; Animals; CLP-model; Cecum; Ligation; borax; boric acid; cytokine; sepsis; septic shock; CLP-model; PTEN Phosphohydrolase; Articles; Rats; MicroRNAs; Disease Models, Animal; Liver; Gene Expression Regulation; septic shock; Proto-Oncogene Proteins c-akt; boric acid; Signal Transduction